EFFECTS OF ALTERNATE NOSTRIL BREATHING ON CARDIORESPIRATORY VARIABLE IN HEALTHY YOUNG ADULTS. - ANUPKUMAR DADARAO DHANVIJAY; NITIN DHOKNE; ARBIND KUMAR CHOUDHARY; SADAWARTE SAHEBRAO KISHANRAO; LALITA CHANDAN (International Journal of Pharma and Bio Sciences, 2015)
Pranayama gradually diminish sympathetic dominance, resulting in better balance between sympathetic and parasympathetic system. In the present study, our aim of practicing alternate nostril breathing exercises (Nadi shodhana pranayama) is to achieve positive body health. In the present study an attempt has been made to investigate the effect of Alternate Nostril Breathing for 12-weeks on some cardio-respiratory parameters such as pulse rate, blood pressure, respiratory rate, Peak Expiratory Flow Rate on healthy young volunteers. We observed, Nadi shodhana pranayama caused reduction in pulse rate, respiratory rate and increase in Peak Expiratory Flow Rate. There was a reduction in systolic and diastolic blood pressure in total population (both males and females). Therefore, this simple exercise can be prescribed to hypertensive patients (with proper monitoring) along with the medical therapy. The increase in PEFR by alternate nostril breathing practice obviously offers an increment in cardiorespiratory efficiency and it can be advocated to the patients of early bronchitis and as a preventive measure for COPD.